Current State and Future Prospects of Hydro Energy in Russia - Bogoviz, Aleksei V.; Lobova, Svetlana V.; Alekseev, Alexander N. (International Journal of Energy Economics and Policy, 2020)
The authors argue that the contemporary scholarship on hydro energy in Russia lacks a comprehensive overview of development trends, global and regional challenges, and future prospects in connection with the ongoing processes in other sectors of the national economy. Consequently, this paper addresses the gap existing in the scholarship by providing a holistic view of the current state of Russia’s hydro energy. It also identifies and discusses the key developmental constraints, including the general economic and political situation developing both in Russia and in the world, negative trends in the country’s wholesale electricity market and the long-term capacity market, the Russian Government’s focus on development of nuclear power stations and not hydroelectric power stations, as well problems of ensuring the technical and environmental safety of hydropower facilities. Finally, the paper outlines prospects of hydro energy in Russia, taking into account global, regional, and national trends in energy development Keywords: Hydro energy, strategy, development, constrains, Siberia, Russian Far East JEL Classifications: Q25, Q48 DOI: https://doi.org/10.32479/ijeep.8968